Structural elements of primary CCR5-using HIV-1 gp120 proteins influencing sensitivity and resistance to the broadly neutralizing monoclonal antibody b12 - Sterjovski, J.; Churchill, M.; Ellett, A.; Wesselingh, S.; Ramsland, Paul; Gorry, P. (2012)
Structure-guided approaches to HIV-1 vaccine design depend on knowledge of the presentation of neutralizing epitopes on gp120, such as the epitope for the broadly neutralizing mAb b12. Here, we characterized predicted three-dimensional structures of functionally diverse gp120 proteins in their b12-bound conformation, to better understand the gp120 determinants that expose or occlude the b12 epitope. Mapping the gp120-b12 binding interface identified amino acid polymorphisms within the C2, C3, C4 and V5 regions of gp120 associated with augmented b12 binding, and importantly, identified residues in the b12-exclusive binding domain of gp120 that are important for b12 neutralization resistance. Structural studies suggest that these b12 resistance variants promote reduced conformational flexibility in the b12 recognition site, which we show involves structural alterations within the gp120 CD4 binding loop and the V4 loop. Together, our studies provide new mechanistic insights into the gp120 determinants influencing sensitivity and resistance to HIV-1 neutralization by b12. © 2012 Elsevier Inc.